2021
DOI: 10.3390/toxins13090670
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Fusarium Species and Mycotoxins in Oat Grains from Manitoba, Canada

Abstract: Fusarium head blight (FHB) can lead to dramatic yield losses and mycotoxin contamination in small grain cereals in Canada. To assess the extent and severity of FHB in oat, samples collected from 168 commercial oat fields in the province of Manitoba, Canada, during 2016–2018 were analyzed for the occurrence of Fusarium head blight and associated mycotoxins. Through morphological and molecular analysis, F. poae was found to be the predominant Fusarium species affecting oat, followed by F. graminearum, F. sporotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 60 publications
2
22
0
1
Order By: Relevance
“…Therefore, F. poae had been considered a weak pathogen on cereals. However, recent studies show F. poae has become omnipresent in Europe, South America, and North America [ 36 , 37 , 38 ], which raises concerns about the importance of this pathogen in the FHB disease complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, F. poae had been considered a weak pathogen on cereals. However, recent studies show F. poae has become omnipresent in Europe, South America, and North America [ 36 , 37 , 38 ], which raises concerns about the importance of this pathogen in the FHB disease complex.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the findings of Yli-Mattila et al [ 42 ], where a similar high correlation in barley samples from Finland and Russia was observed. Islam et al [ 37 ] reported correlations between NIV content and the concentration of F. poae DNA in oat samples from Manitoba. These results suggest F. poae is a potent NIV producer in barley.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichothecenes are classified into groups A and B according to the presence of different substitutions at the C-8 position of the molecule’s backbone [ 7 ]. Over the last decade the most prevalent mycotoxins in oat have been deoxynivalenol (DON) (group B trichothecene) and T-2 toxin, together with its hydrolysed form HT-2 toxin (belonging to the highly toxic group A trichothecenes) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. DON accumulating in oat is produced mostly by F. graminearum [ 15 , 16 ], while the main producers of T-2/HT-2 toxins are F. langsethiae and F. sporotrichoides [ 11 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade the most prevalent mycotoxins in oat have been deoxynivalenol (DON) (group B trichothecene) and T-2 toxin, together with its hydrolysed form HT-2 toxin (belonging to the highly toxic group A trichothecenes) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. DON accumulating in oat is produced mostly by F. graminearum [ 15 , 16 ], while the main producers of T-2/HT-2 toxins are F. langsethiae and F. sporotrichoides [ 11 , 17 , 18 , 19 ]. There is a strong tendency for the opposing occurrence of DON and T-2/HT-2 toxins in oat, depending on the weather and agricultural practices [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%